Women's mountaineering: accessing participation benefits through constraint negotiation strategies. Issue 5 (2nd September 2020) - Doran, A.; Schofield, P.; Low, T.
ABSTRACT: The purpose of this study is to investigate the strategies women use to negotiate mountaineering participation constraints and the resultant benefits from participation. Survey responses from 321 female mountaineers produced four constraint negotiation dimensions and three participation benefit dimensions using confirmatory factor analysis. Three of the four negotiation dimensions support earlier findings in the literature on women's experiences of adventure activities. The identification of a fourth dimension relating to 'confidence and adaptation' represents a new contribution. Similarly, the three benefit dimensions largely support existing literature. However, some benefits loaded on different dimensions to what has previously been reported and verifying the influence of each negotiation dimension on specific benefit dimensions also represents an original contribution. Therefore, this study extends our understanding of female adventure participants and quantitatively verifies women's constraint negotiation and participation benefits in the context of mountaineering. Accordingly, this study makes an important theoretical contribution to the understanding of women's adventure experiences in mountaineering, which may be of interest to others researching female participation in other adventure activities. The findings also suggest that mountaineering is a space that is being used as a means to resist gendered expectations and to gain empowerment.